2018
DOI: 10.1159/000488399
|View full text |Cite
|
Sign up to set email alerts
|

Suctioning Minimally Invasive Percutaneous Nephrolithotomy with a Patented System Is Effective to Treat Renal Staghorn Calculi: A Prospective Multicenter Study

Abstract: Objectives: To investigate the safety, efficacy, and practicability of minimally invasive percutaneous nephrolithotomy (MPCNL) with the aid of a patented irrigation clearance system in treating renal staghorn calculi. Methods: From August 2009 to July 2014, 4 hospitals had executed a prospective multicenter study with a total of 912 cases. The patients were randomly divided into 3 groups: suctioning MPCNL, standard percutaneous nephrolithotomy (PCNL), and traditional MPCNL groups. Multiple operative and periop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 10 publications
1
50
0
Order By: Relevance
“…We also excluded from our analysis: one article with insu cient data, one article without full text, and one review article. Finally, three randomized controlled trials (RCTs) and two case-controlled trials (CCTs) with 1163 patients that satis ed all the inclusion criteria were subjected to the meta-analysis [15][16][17][18][19]. The article selection process was followed by the PRISMA statement (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also excluded from our analysis: one article with insu cient data, one article without full text, and one review article. Finally, three randomized controlled trials (RCTs) and two case-controlled trials (CCTs) with 1163 patients that satis ed all the inclusion criteria were subjected to the meta-analysis [15][16][17][18][19]. The article selection process was followed by the PRISMA statement (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…The JADAD score for three studies was 2, 3, and 4. One study is of low quality as no blinding was used and the report of explanation of the speci c method of randomization [15,16,19]. The MINORS score for the two studies were 20 and 22, respectively [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, the main reasons for urosepsis are the following: (1) MPCNL has been performed on patients with UTI before the infection is fully controlled; (2) the possibility of live pathogenic bacteria in infectious stones; (3) complex renal stones, with heavy loads and a long operation time; (4) excessively high intrarenal pressure intraoperatively [19][20][21][22][23]. In this study, we focused on patients who underwent MPCNL with preoperative UTI for a more sensitive and effective observation of the impacts of surgical factors on sepsis, aiming to reduce sepsis incidence by improving surgical procedures and methods.…”
Section: Discussionmentioning
confidence: 99%
“…e longer the operative time, the higher the risk of sepsis. Previous studies have also revealed that the risk of infection is significantly increased with a surgical time longer than 90 min during PCNL [17,19]. Operative time mainly depends on stone loads and channel size.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that about half of PCNL in children using adult-type instruments have no serious complications. Although MPCNL is already widely accepted, the system is mainly used to remove stones by high pressure perfusion or manual excision with forceps, resulting in intraoperative or postoperative fever, sepsis or septic shock [21], in addition to complications such as hemorrhage and extravasation [22]. MPCNL postoperative indwelling nephrostomy will sometimes lead to pain and nursing requirements.…”
Section: Discussionmentioning
confidence: 99%